(untitled) (Experimental biology, 2024)
The collapse of agricultural infrastructure in Kazakhstan and other countries worldwide has resulted in the transfer of ownership or abandonment of plant protection chemicals storage facilities. Despite legislative measures and international conventions, the issue of persistent organic pollutants (POPs) remains unresolved. Measures to restore POP-pesticide-contaminated areas present limited options. Hence phytotechnology emerges as a promising strategy due to eco-friendliness and the absence of significant capital investments. One of the key aspects of technology is the search for novel plant species capable of accumulating and transforming these contaminants into less toxic compounds. Current study investigated the potential of the energy crop Miscanthus sinensis Anderson (M. sinensis) as a novel phyto plant for remediating POP-pesticide-contaminated soils. The experimental layout comprised cultivation of M. sinensis in POP-pesticide-contaminated (2.4-DDD, 4.4-DDD, 4.4-DDE, 4.4-DDT, α-HCH, β-HCH, γ-HCH, and δ-HCH) soil. Biomass productivity, physiological parameters, and phytoremediation potential were assessed at harvest. Our findings revealed that POP-pesticides influenced productive and physiological parameters of M. sinensis differently, specifically: reduced aboveground biomass and chlorophyll pigments content by up to 23 and 37%, respectively, and increased root biomass by up to 17%. Furthermore, the plant exhibited a remarkable tolerance to severe POP-pesticide contamination, as evidenced by a tolerance index of 0.99. Evaluation of phytoremediation coefficients revealed that M. sinensis employed distinct strategies depending on POP-pesticide: phytoextraction and phytostabilisation. 4.4-DDT, β-HCH, and γ-HCH were accumulated in aboveground biomass with translocation factors of 1.18, 4.04, and 84.0, respectively. Whereas metabolite 4.4-DDE was accumulated in plant roots with a bioconcentration factor of 2.07. Study results suggest that M. sinensis holds great promise for use in POP-pesticides phytoremediation projects, particularly in Kazakhstan, owing to confirmed phytostabilisation activity concerning 4.4-DDE, the final metabolite of 4.4-DDT degradation. Therefore, further research should focus on optimizing M. sinensis phytostabilisation strategies for other POP-pesticides.